Impact of the Change Starts at Home Trial on Women's experience of intimate partner violence in Nepal. (April 2020) - Clark, Cari Jo; Shrestha, Binita; Ferguson, Gemma; Shrestha, Prabin Nanicha; Calvert, Collin; Gupta, Jhumka; Batayeh, Brian; Bergenfeld, Irina; Oakes, J. Michael
Abstract: Intimate partner violence (IPV) affects 1 in 3 women worldwide. Research in low- and middle-income countries suggests that multicomponent interventions incorporating media, group work, and community mobilization may be effective at changing social norms that enable such violence. Our study aimed to evaluate the impact of a radio programme plus community engagement versus radio programming alone on the 12-month prevalence of IPV. Using a cluster randomized, repeat cross-sectional, single-blinded approach, thirty-six village communities were pair-matched within three districts in Nepal and randomly assigned to either control or intervention. Both groups were exposed to social behaviour change communication through radio programming. In addition, weekly listening and discussion groups (LDGs) were formed in intervention communities to meet and discuss radio programming over the 40-week intervention period. Participants were also exposed to other community mobilization activities such as street theatre and messaging from local leaders who were engaged in intervention programming. IPV was measured at baseline, 12 months post-baseline at program conclusion, and 28 months post-baseline using a simple random sample of 40 married women per cluster (n = approximately 1440 at each time point) along with 382 women who participated in the LDGs. Although control and intervention groups were demographically similar, baseline rates of IPV were higher in control areas. The trend in IPV for both groups was nonlinear, largely declining at midline (control condition) and rising again at endline (control and intervention conditions), possibly reflecting greater reporting due to awareness-raising activities. Significant differences between the two groups were largely absent at endline. Higher LDG attendance was associated with decreases in several forms of IPV, some of which persisted to endline. These findings suggest that intensive community engagement over longer timespans or social network measurement may be necessary to detect significant changes at the community level (NCT02942433). Highlights: IPV was higher in control communities at baseline despite demographic balance. IPV had decreased in only control communities at programme conclusion. Differences in treatment arms at conclusion did not persist to endline. High participation was linked declines in IPV at program conclusion and endline. Interviews showed sustained improvements in relationship quality and other mediators.